Empowering clean water whilst safeguarding water distribution pipeline integrity: towards manganese- and iron-free lime hydrate for water treatment. Issue 3 (20th January 2023) - Kocsis, Dávid; Ward, Rhys A.; Meyer, Christopher R.; Thompson, Michael; Prior, Timothy J.; Kelly, Stephen M.; Lawrence, Nathan S.; Wadhawan, Jay D.
Abstract : Active and passive manganese and iron impurities in drinking water-grade lime hydrate are removed through redox treatment. Abstract : Hydrated limes are amongst the most economically valuable alkalis used by the water industry for the treatment of potable water. They are typically manufactured from the thermal decomposition of high purity limestones. However, the latter contain both manganese and iron impurities, which are transformed into the oxides Mn3 O4 and Fe2 O3 on burning in kilns (between 900–1100 °C) during the manufacture of lime, and are retained in the lime hydrate upon slaking. These impurities can be released through oxidation by conventional water disinfection chemicals (such as alkaline hypochlorite) during the use of lime hydrate as the alkaline pH modifier during conventional operations in water treatment works. This work investigates the redox mechanisms for manganese and iron removal from lime hydrate using alkaline hypochlorite: for manganese, interfacial electron transfer occurs first leading to dissolution as permanganate; in the case of iron impurities, solubility is encouraged in oxygenated solutions first through formation of solid ferrite, with oxidative dissolution of ferrite to ferrate. As expected for activation-controlled reactions, the oxidative dissolution is enhanced with increased temperatures; mapping the dissolution process with time allows for the unravelling of "rule-of-thumb" relationships for impurity removal of ∼1% min −1 for manganese and ∼3% min −1 for iron at 90 °C in alkaline hypochlorite.